Respostas

2013-12-08T12:45:15-02:00
f(x)=3x-12
3x-12=0
3x=12
x=12/3
x=4

f(x)=-x=9
-x-9=0
-x=9   (-1)
x=-9

f(x)=
x²-5x+6=0
Δ = b² -4ac
Δ = (-5)² -4 *1 * 6
Δ = 25 -24
Δ = 1
x' = (-b + √∆)/ 2a
(-(-5) + 1)/2 * 1
(5 + 1)/2
6/2= 3
x'' = (-b - √∆)/ 2a
(-(-5) - 1)/2 * 1
(5 - 1)/2
4/2= 2        ( Tanto 3 e 2 valem como resposta)

f(x)= x
²-7x+10
x²-7x+10=0

Δ = b² -4ac
Δ = (-7)² -4 *1 * 10
Δ = 49 -40
Δ = 9
x' = (-b + √∆)/ 2a
(-(-7) + 3)/2 * 1
(7 + 3)/2
10/2= 5
x'' = (-b - √∆)/ 2a
(-(-7) - 3)/2 * 1
(7 - 3)/2
4/2= 2          ( Ambos também valem).


1 5 1